Determining the Safety and Effectiveness of Electrocautery Enhanced Scissors for Peroral Endoscopic Myotomy (with Video) - Kelly E. Hathorn; Walter W. Chan; Hiroyuki Aihara; Christopher C. Thompson (Korean Society of Gastrointestinal Endoscopy, 2020)
Background/Aims: Peroral endoscopic myotomy (POEM) has recently come to the forefront in the management of achalasia. We aimed to analyze the efficacy and safety of the use of electrocautery enhanced scissors (EES) for POEM. Methods: This retrospective cohort study prospectively collected the data of all adult patients (aged ≥18 years) with normal foregut anatomy who underwent POEM using EES. The patients' baseline characteristics and procedure details (time, tunnel length, myotomy length, depth, and location) were recorded. The primary outcome was clinical success (3-month post-procedure Eckardt score of ≤3). The secondary outcomes were technical success and adverse events. A paired Student's t-test was performed. Results: Fifteen patients were included in this study. The technical success rate of myotomy using EES was 100%. Fellows participated in the myotomy in all cases. The clinical success rate was 93.3% (14/15). The mean pre-Eckardt score was 5.4±2.5, while the mean post-Eckardt score was 1.3±1.3, which indicated a significant improvement (p≤0.0001). The most common treatment-related adverse events were post-procedure pain (4, 26.7%) and symptomatic reflux disease (4, 26.7%). Conclusions: In the largest series to date on the use of EES in POEM, we demonstrated that this technique has both technical and clinical efficacy as well as an excellent safety profile.